HUBUNGAN ANTARA INTENSITAS MENONTON REALITY SHOW DENGAN KECENDERUNGAN PERILAKU PROSOSIAL PADA REMAJA - Frisnawati, Awalia (EMPATHY Jurnal Fakultas Psikologi, 2012)
ABSTRACT This study is aims to determine the relationship between the intensity of watching a reality show with the trend of prosocial behavior in adolescents. Data collection methods that was used in this study is quantitative method. Data analysis technique that was used in this study is the Pearson product moment correlation by using SPSS version 16.0 for Windows. Product moment correlation analysis found that there is a significant positive relationship between the intensity of watching a reality show with the trend of prosocial behavior in adolescents (r = 0.315 p = 0.004). the contribution of the intensity of watching reality shows is 9.9%  to the tendency of prosocial behavior in adolescents, while 90.1% influenced by other variables. Based on the research results it can be concluded that there is a very significant positive relationship between the intensity of watching a reality show with the trend of prosocial behavior in adolescents.   Keywords: intensity watching, prosocial behavior tendency, reality shows.